Within-subject correlation between salivary IgA and measures of training load in elite football players - Figueiredo, P.; Nassis, G. P.; Brito, J. (International Journal of Sports Physiology and Performance, 2019)
Salivary secretory immunoglobulin A (sIgA) provides a noninvasive biological marker that may be useful to monitor football players responses to training and to identify players at risk of upper respiratory tract (URT) infection. Indeed, low levels of salivary IgA over a training period and decreased IgA secretion rate have been associated with higher risk of URT infection in athletes.